Photoexcited Pd(ii) auxiliaries enable light-induced control in C(sp3)–H bond functionalisation. Issue 9 (30th January 2020) - Czyz, Milena L.; Weragoda, Geethika K.; Horngren, Tyra H.; Connell, Timothy U.; Gomez, Daniel; O'Hair, Richard A. J.; Polyzos, Anastasios
Abstract : Visible light irradiation of 8-aminoquinoline Pd(ii ) complexes initiates photoinduced electron transfer with alkyl halides, affording C–H halogenation over C–C bond adducts. A method for inert C(sp 3 )–H bond halogenation (Br, Cl and I) is reported. Abstract : Herein we report the photophysical and photochemical properties of palladacycle complexes derived from 8-aminoquinoline ligands, commonly used auxiliaries in C–H activation. Spectroscopic, electrochemical and computational studies reveal that visible light irradiation induces a mixed LLCT/MLCT charge transfer providing access to synthetically relevant Pd(iii )/Pd(iv ) redox couples. The Pd(ii ) complex undergoes photoinduced electron transfer with alkyl halides generating C(sp 3 )–H halogenation products rather than C–C bond adducts. Online photochemical ESI-MS analysis implicates participation of a mononuclear Pd(iii ) species which promotes C–X bond formation via a distinct Pd(iii )/Pd(iv ) pathway. To demonstrate the synthetic utility, we developed a general method for inert C(sp 3 )–H bond bromination, chlorination and iodination with alkyl halides. This new strategy in auxiliary-directed C–H activation provides predictable and controllable access to distinct reactivity pathways proceeding via Pd(iii )/Pd(iv ) redox couples induced by visible light irradiation.